Potential of payment for ecosystem services (PES) for the conservation of the Layawan watershed in upland communities in Misamis Occidental, Philippines - Llanza, Mae Belen C.; Lasco, Rodel D.; Calderon, Margaret M.; Ancog, Rico C.; Anit, Kharmina A.; Salvador, Myranel G. (2016)
The Layawan Watershed is one of the important major rivers emanating from Mt. Malindang Range Natural Park (MMNRP) that supplies water to Oroquieta City and nearby towns. Over
the years, different anthropogenic activities, together with changing global climate, negatively affected the park. Studies show that the water produced by the watershed has been decreasing, while the demand for water is increasing. Thus, there is a need to conserve and protect the Layawan Watershed to prevent further degradation and ensure the sustainable production of ecosystem services. This paper analyzed willingness of upland communities to participate in the Layawan Watershed Conservation and Management Program (LWCMP). A contingent valuation survey involving 110 respondents from
six upland barangays of Oroquieta City was conducted to evaluate: the respondents’ awareness about and perceptions towards the conservation and protection of the Layawan
Watershed, their openness to and opportunity costs that would be incurred if they would adopt new conservation techniques, and their willingness to accept (WTA) compensation. The results of the study show that 99% of the respondents are willing to participate in the LWCMP despite the fact that their land will be subjected to a permanent conservation easement. In general, the Subanen tribe had a positive perception and feelings towards
the different statements provided in the survey. They agreed on most of the statements and have identified provision of fresh water for drinking, domestic, agricultural and industrial uses as an important watershed service (90%). The total average willingness to accept compensation revealed in the survey (PhP 3,050/month) is higher by 56% compared to the total average farm income (PhP 1,334/month). Furthermore, the WTA amount
elicited is higher by 5% compared to the total average households’ income (PhP 2,887). The high level of willingness to participate in the conservation program presents great
potential in implementing a Payment for Ecosystem Services (PES) scheme in Layawan Watershed.
Keywords: Watershed management